Is sexual attraction and place of origin a moderator of sex in pornography consumption? Cross-sectional study on a representative sample of young adults - Belén Sanz-Barbero; Vanesa Pérez-Martínez; J. Francisco Estévez-García; Carmen Vives-Cases (BMC, 2023)
Abstract Background Pornography consumption is higher in men, but we do not know if this association can be modified by different variables, such as sexual attraction and place of origin. Given the impact pornography has on minors, there are limited studies that analyze the use of pornography in representative samples of the adult population. The aim was analyze the prevalence and factors associated with using pornography in young adult men and women, living in Spain, with different sexual attractions and different places of birth. Methods Cross-sectional study with an online survey conducted with 2515 men and women aged between 18 and 35 years of age. The prevalence of pornography consumption is described and analyzed in the total sample and stratified by sex, according to socio-demographic and sexual attraction variables. The association between covariates and pornography consumption at some point in life was estimated with prevalence ratios (PR) obtained with the Poisson models of robust variance. Dependent variable: voluntarily using pornography at some point in life. Socio-demographic variables were included in the analysis: age, sex, level of education, place of birth. Sexual attraction was also analyzed. Results In Spain, 94.7% of men between 18 and 34 years and 74.6% of women have voluntarily used pornography at some point in their life. The mean age to start using it is earlier in men [Mean:14.2; Standard Deviation (SD):2.3]. Bisexual/homosexual attraction (reference: heterosexual) increases the probability of using pornography in women [(PR (95%CI): 1.30 (1.22; 1.38)]. Yet this is not observed in men. In both sexes, the probability of using pornography increases with age [(PR (95%CI): 1.01(1.00; 1.01)] and coming from abroad (reference: native), being the effect of country of birth significantly higher in women [(PR (95%CI): 1.17 (1.09; 1.26)] than in men [(PR (95%CI): 1.04 (1.01; 1.07). Conclusions Public health programmes aimed at improving affective-sexual health should consider the high use of pornography among young adults in Spain, as well as those variables that increase its use.